Senior High School Studentsâ Problems in Writing: A Preliminary Study of Implementing Writing E-Journal as Self Assessment to Promote Studentsâ Writing Skill - Novariana, Hanna; Sumardi, Sumardi; Tarjana, Sri Samiati (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The study is aimed to investigate the internal and external problems in Writing by the Senior High Students in one of the school in Indonesia. The sample of this study is the eleventh grade students having low ability in Writing. This research is a qualitative study using purposive sample. In collecting the qualitative data the researchers did observation, and distributed questionnaire. This study reveals some findings related to the studentsâ low ability in writing. There are internal problems which came from the students, such as: 1) the low motivations in learning English, 2) the difficulty to choose the appropriate words in writing, 2) the lack of vocabulary, 3) the difficulty to arrange words in the appropriate order, 4) the difficulty to spell the words, 5) the difficulty to write the sentences in appropriate grammar, and 6) the tendency to be passive learners in classroom activities. The external problems come from the students are: 1) the lack of practice, and 2) there is no feedback on their writing. The result indicates the most internal and external problems faced by students in writing class and the impacts of studentsâ understanding of their writing problems in implementing writing e-journal as self assessment to promote studentsâ writing skills. Furthermore, the paper concludes with some guidelines for students how to face their own problems in writing.